Properties and rapid sintering of a nanostructured tetragonal zirconia composites - Shon, In-Jin; Yoon, Jin-Kook; Hong, Kyung-Tae (KOREAN INST METALS MATERIALS, 2017)
4YSZ is generally used as oxygen sensors, fuel cells, thermal barrier and hip and knee joint replacements as a result of these excellent properties with its high biocompatibility, low density, good resistance against corrosion, high ionic conductivity, hard phase and melting point. However, 4YTZ with coarse grain has low resistance to wear and abrasion because of low hardness and low fracture toughness at room temperature. The fracture toughness and hardness of a 4YTZ can be improved by forming nanostructured composites and addition of a second hard phase. In this study, nanostuctured 4YTZ-graphene composites with nearly full density were achieved using high-frequency induction heated sintering for one min at a pressure of 80 MPa. The rapid consolidation and addition of graphene to 4YTZ retained the nano-scale structure of the ceramic by inhibiting grain growth. The grain size of 4YTZ was reduced remarkably by the addition of graphene and the addition of graphene to 4YTZ greatly improved the fracture toughness without decrease of hardness.
Keywords: OXIDE FUEL-CELLS; ENHANCED MECHANICAL-PROPERTIES; YTTRIA-STABILIZED ZIRCONIA; GRAPHENE; POWDERS; GROWTH; CONSOLIDATION; CONDUCTIVITY; PRECURSORS; MEMBRANES